Clinical case study of Kearns–Sayre syndrome: diagnosis, methods of treatment - S. V. Vlasenko; E. N. Ponomarenko; G. M. Kushnir; L. L. Korsunskaya; N. V. Larina; V. V. Shalanin; N. I. Usulceva (Нервно-мышечные болезни, 2018)
The article outlines the current knowledge of the etiology, pathogenesis, clinical features and diagnostic criteria of one of the forms of mitochondrial encephalomyopathy – the Kearns–Sayre syndrome. The observation of a patient with an incomplete case of the Kearns–Sayre syndrome is presented. The complexity of diagnosis and the range of differential diagnostic search as well as approaches to treatment with the use of neurotrophic factors are widely discussed in the research.